Analysis of the plant sector in Giurgiu county in the period 2015-2019: Gaps towards the Sud-Muntemia region - Andreea-Daniela Giucă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The geographical location of the Sud-Muntenia region and its relief ensure favorable natural conditions for vegetable crops, especially those in the cereals category, determining the predominantly agrarian character of the region, over 70% of the total area of the region is agricultural area. Agriculture is the basic economic sector for the counties in the southern part of the region - Arge÷s, Prahova, Dâmbovi÷ta, Cæalæara÷si, Ialomi÷ta, Teleorman and Giurgiu. As a result of this situation, the plant sector has experienced a continuous development in the recent years, becoming one of the important branches of agricultural production in the region. The objectives of the paper aim to provide an overview of the agricultural plant sector of Giurgiu county, compared to the Sud-Muntenia region. The paper analyzes the evolution of cultivated areas with the main vegetable crops representative of the South-Muntenia region and especially of Giurgiu county (wheat and rye, barley and barley, corn, sunflo er and rapeseed) and productions, in the period 2015-2019. Thus, based on the data provided and processed by the National Institute of Statistics and the Agricultural Directorate of Giurgiu County and their interpretation through the methods of statistical analysis, the oscillations that occurred during this period were highlighted.
Keywords: Q10; R14; 330; vegetable agricultural sector; surface; output; Giurgiu county; Sud-Muntenia region